The assessment of quality service of Starbucks coffee shop as perceived by the customers - Amoncio, Mylene; Ermalyn, Dalina (Parañaque City: Olivarez College, 2008)
Statement of the Problem The study aimed to assess the quality service of Starbucks Coffee Shop as perceived by the customers. Specifically, this sought to answer the following questions: What is the demographic profile of the customers in terms of age, gender, occupation and civil status, what is the extent of the effectiveness of the service crew as perceived by the customers, how is the effectiveness of the ambiance of Starbucks, does the management of Starbucks initiates quality service to the customers, is there a significant observation of the customers with regards to quality service. Findings Based on the respondents profile, majority of the respondents are in the age bracket of 18-20 years old with 40%, most of them are female with 65%, majority of them are students with 70%, single respondents are 80%, the crew of the Starbucks give their moderately service to the customers with 60% and 40% served effectively. There is an effectiveness of the ambiance to attract the costumers of the Starbucks Coffee Shop. It revealed that 80% very effective and 20% effective. The management of the Starbucks had their initiative to give quality service. It revealed that 100% agreed of giving quality service to the customers. Conclusions The Starbucks coffee shop has standard of quality service. This is the reason most of the customers in all walks of life patronized Starbucks Coffee shop. The Starbucks Coffee shop proves that the quality service being rendered by the staff including the management is moderately effective and well adjacent to their coffee experience, the Starbucks Coffee shop truly offers authentic coffee experience that conveyed the artistry of espresso making, a place to think and imagine, a spot where people could gather and talk over a great cup of coffee, a comforting refuge that provided a sense of community, a third place for people to congregate beyond work or the home, a place that welcomed people and rewarded them for coming, and a layout that could accommodate both fast service and quiet moments, the Starbucks crew required more than just simply pouring coffee into a cup; it is providing a superior standard of customer service and coffee beverages that surpassed all other coffee providers in order to make a lasting impression on each and every customer served. It is essential to make each and every customer feel welcome and appreciated so that they will not only come back, but so that they have truly experienced Starbucks as a "third place" - a home away from home. Recommendations The researchers recommend the following in connection with this study. Hired people who have the drive, talents, skills and personality that you need. With the best people, you can concentrate on developing their talents and managing their performance right from their first day on the job, the researchers recommend the right tools which are positive orientation, experience, and a training plan. It should be followed with clear goals, understandable directions and frequent feedback. Adding in the chance to grow, the opportunity to develop skills and the likelihood for advancement will create a dedicated, enthusiastic employee, the researchers recommend to the management to set their goals in order to achieve the improvement and succeed. In order for that to happen, managers and employees have to work together and communicate to be able to recognize obstacles to success, and to make solutions to overcome those obstacles. Documenting in a logbook all critical incidents, complaints, customers' comments and concerns consolidated by the manager or supervisor to be discussed during meetings and briefings so that the staff will be alerted of operational deficiencies and take corrective measures, Service staff should carry themselves in a professional manner to make a good impression. Service staff reflected the image of the company. In addition the management should monitor the performance of the staff and sees to it that they follow the standard procedures and abide by existing house rules.
Undergraduate Thesis